The impact of changing graphic settings on performance in selected video games - Stanik, Łukasz; Miłosz, Marek (Journal of Computer Sciences Institute, 2025)
This article presents the results of research into the impact of changing graphics settings on the performance of PC games. Three leading titles were selected for the study, each representing a different type of gameplay: Assassin’s Creed Odyssey, Shadow of the Tomb Raider, and Cyberpunk 2077. The key parameter for evaluation was the frame rate (frames per second, FPS). The findings allow for an assessment of how changes in settings such as texture quality, anti-aliasing, and special effects influence game performance. Based on the results, recommendations were developed for both gamers and game developers.